Integrating indigenous knowledge practices as context and concepts for the learning of curriculum science: A methodological exploration - Caleb Mandikonza (Environmental Association of Southern Africa, 2019)
Teachers and learners bring tacit as well as explicit knowledge into learning contexts. In the science classroom, learners' tacit knowledge can involve sustainability practices that have been passed down for many generations and that have enabled people to survive in their particular environment and derive benefit from it. This study examines an example of such a practice that was observed in a rural community. The study sought to establish whether such a sustainability practice could be incorporated into the formal science teacher training classroom with a view to broadening the teaching and learning of science curriculum concepts. The study was conducted through observation of rural participants as they conducted certain sustainability practices as well as through interviews with the same participants. Student teachers preparing for lesson planning and teaching presentations (as part of their peer-teaching activities) engaged with these sustainability practices in a six-phase process. Socio-cultural approaches guided the analysis. The study showed that, through a carefully considered methodological approach, it was possible to use those practices with which learners were familiar in their daily lives -that is, their habitual indigenous knowledge practices (IKPs) - to unpack and explain related scientific concepts from the school science curriculum in the classroom (habitual practices of classroom science) (Bourdieu, 1998). Accordingly, the study illustrated how knowledge of science can be developed from context to concept. The study was only conducted with student teachers in a peer-teaching context, but it would be interesting to investigate how such an approach could be used by student teachers during their teaching practice as well as by teachers at secondary-school level.